Equivalent linear elastic-viscous model of shape memory alloy for isolated structures. (September 2016) - Ghodke, Sharad; Jangid, R.S.
Abstract: In this investigation, the equivalent linear elastic-viscous model of shape memory alloy (SMA) is established for seismic analysis of base-isolated structures using system identification method. The necessary key parameters to express the hysteresis loop of SMA are austenite stiffness, transformation strength, ductility ratio, and stiffness ratio. These parameters are considered in the modeling. This model is developed based on the American Association of State Highway and Transportation Officials (AASHTO) isolation guidelines. In order to validate the proposed model, the base-isolated benchmark building is analyzed by using proposed equivalent linear SMA model as well as the different non-linear SMA models. The evaluation criteria given in the benchmark problem and time variation of top-floor absolute accelerations and base-displacements are considered for comparing the linear and nonlinear models of SMA. An excellent agreement is achieved between proposed equivalent linear SMA model and its nonlinear models. The seismic code recommends that the equivalent linear model of the nonlinear system can be used for carry out the response spectrum analysis of base-isolated structures. Furthermore, the non-linear model requires computationally more time and effort, especially for larger degrees of freedom system. The proposed model may be useful to design engineers in order to over come the disadvantage of non-linear models.